2020
DOI: 10.3390/vaccines8040715
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Cytokines IL-7-Linker-IL-15 Promote Mycobacterium Tuberculosis Subunit Vaccine to Induce Central Memory like T Cell-Mediated Immunity

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis (M. tuberculosis), is among the most serious infectious diseases worldwide. Adjuvanted protein subunit vaccines have been demonstrated as a kind of promising novel vaccine. This study proposed to investigate whether cytokines interliukine-7 (IL-7) and interliukine-15 (IL-15) help TB subunit vaccines induce long-term cell-mediated immune responses, which are required for vaccination against TB. In this study, mice were immunized with the M. tuberculosis pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Our findings showed that the TB/Prex-SCoV-2 group had lower amounts of systemic soluble factors such GM-CSF ( 29 ), IL-15 ( 30 ), IL-1β ( 31 ), IL-7 ( 30 ), TNF-β ( 32 ), IL-12(p70) ( 33 ), IL-17 all of which are considered essential for Mtb control ( 34 ). Nevertheless, there was no difference in the bacillary load in sputum when compared to the TB group.…”
Section: Discussionmentioning
confidence: 77%
“…Our findings showed that the TB/Prex-SCoV-2 group had lower amounts of systemic soluble factors such GM-CSF ( 29 ), IL-15 ( 30 ), IL-1β ( 31 ), IL-7 ( 30 ), TNF-β ( 32 ), IL-12(p70) ( 33 ), IL-17 all of which are considered essential for Mtb control ( 34 ). Nevertheless, there was no difference in the bacillary load in sputum when compared to the TB group.…”
Section: Discussionmentioning
confidence: 77%
“…Phosphodiesterase inhibitors inhibit MDSC (42), as does priming with systemic poly IC-LC (19). Administration of cytokines such as IL-7 and IL-15 could promote T cell functioning (43).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, recombinant NDV expressing mIL-7/ mIL-15 also improved the anti-tumor activity of the NDV LX strain (166), while the delivery of mIL-7/mIL-15 co-expression plasmids as molecular adjuvants with the Toxoplasma gondii calcium-dependent protein kinase 1 (TgCDPK1) DNA vaccine enhanced Toxoplasma-specific IgG2a levels and CD8 + / CD4 + IFN-g + T cell frequencies induced by the vaccine and prolonged the survival of mice post lethal infection by approximately 7 days (149). Furthermore, mIl-7/mIl-15 genes subcloned into an adenovirus were able to extend the protective efficacy of the M. tuberculosis subunit vaccine (LT70 and MH fusion protein) by augmenting M. tuberculosis-specific central memory-like T cell responses (167). When mIl-7/mIl-2 were coadministered with the ovalbumin (OVA) DNA vaccine, mIL-7 and mIL-2 mutually improved its immunogenicity by upregulating the specific antibody titer, IFN-g production, and T cell proliferation (168).…”
Section: Il-7 Applications In Vaccinesmentioning
confidence: 97%